Personality characteristics, social factors, and identity styles among adolescents in Golestan, Iran - Ghorbani, Alireza (2013)
The present study aims to identify the identity styles and personality characteristics of adolescents. It also seeks to examine the relationship between personality characteristics, moderating variables, and identity styles in adolescents, to compare the differences between gender and age factors influencing the identity styles, and to determine the moderator effect of moderating variables on the relationship between personality characteristics and the adolescents’ identity styles. A quantitative research method was employed. The sample included high school students (n=380) aged 17 and 18. Data were collected through self-administered questionnaires. Descriptive and inferential statistics such as t-test, Pearson correlation and multiple regressions were used. The findings showed there were significant correlations between personality characteristics and identity styles in adolescents. Significant correlations between moderating variables and identity styles in adolescents were also observed. In addition according to the results, a moderate and positive correlation was observed between informational and normative styles, informational style and commitment, normative style and commitment, as well as commitment and neuroticism. To examine the moderator effect of moderating variables on relationship between personality characteristics and the adolescents’ identity styles five stages were proposed. In the first stage peer group relationship significantly moderates the relationship between neuroticism and normative. In the second stage level of education significantly moderates the relationship between extraversion and normative. Additional results also showed that peer group relationship significantly moderates the relationship between extraversion and diffuse identity style. Third,moderational analyses revealed a significant moderational effect for level of education on the association between openness and informational identity style. Fourth, moderating effects of peer group relationship on the association between conscientiousness and informational was found to be significant. Additionally,results showed moderational analysis revealed that the association between conscientiousness and commitment is significantly moderated by family relationship. The last moderational analysis showed significant moderating effects for family relationship and level of education on the relationship between agreeableness and diffuse. Also, indicated that peer group relationship significantly moderates the relationship between agreeableness and commitment. Additionaly, the results of the study supported theories like social cognitive theory,General other theory, and triat approach. The results shed new light on the processes involved in the personality characteristics and moderating variables of adolescents’ styles of identity exploration.